2017
DOI: 10.1016/j.rbmo.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liraglutide on ovarian dysfunction in polycystic ovary syndrome: a randomized clinical trial

Abstract: Polycystic ovary syndrome (PCOS) encompasses an ovarian and a metabolic dysfunction. Glucagon-like peptide-1 (GLP-1) analogues facilitate weight loss and ameliorate metabolic dysfunction in overweight women with PCOS, but their effect on ovarian dysfunction is scarcely reported. In a double-blind, randomized trial, 72 women with PCOS were allocated to intervention with the GLP-1 analogue liraglutide or placebo (1.8 mg/day), in a 2:1 ratio. At baseline and 26-week follow-up, bleeding pattern, levels of AMH, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 28 publications
4
77
0
4
Order By: Relevance
“…GLP-1 agonists also have an established role in obesity due to their effects on appetite and food intake from their actions in the gut to delay gastric emptying and in the brain [ 176 ]. In small studies, the GLP-1 receptor agonist liraglutide has been shown to have beneficial effects in both NAFLD and PCOS [ 177 , 178 ]. The beneficial effects may be secondary to weight loss rather than direct effects on insulin sensitivity and cellular metabolic pathways.…”
Section: Approaches To Prevent or Reverse The Progression From Mhomentioning
confidence: 99%
“…GLP-1 agonists also have an established role in obesity due to their effects on appetite and food intake from their actions in the gut to delay gastric emptying and in the brain [ 176 ]. In small studies, the GLP-1 receptor agonist liraglutide has been shown to have beneficial effects in both NAFLD and PCOS [ 177 , 178 ]. The beneficial effects may be secondary to weight loss rather than direct effects on insulin sensitivity and cellular metabolic pathways.…”
Section: Approaches To Prevent or Reverse The Progression From Mhomentioning
confidence: 99%
“…Der Effekt von Antidiabetika wie Liraglutid und Empagliflozin ist Gegenstand von Studien. Diese weisen vereinzelt positive Daten zur Reduktion von Gewicht, Hyperandrogenämie, Anovulation und zur Schwangerschaftsrate unter IVF auf [16][17][18][19][20]. Der Einsatz ist derzeit als experimentell zu betrachten und für die Patientinnen auch im Rahmen der Indikation der Lifestyle-Medikation oder eines Off-Label-Use kostenintensiv.…”
Section: Ausblickunclassified
“…The most recent study reported that liraglutide improved bleeding ratio and decreased ovarian volume with liraglutide when compared to placebo [61]. Moreover, after liraglutide discontinuation, one small 12-week study conducted with 40 infertile PCOS reported an increase of fertility potential.…”
Section: Rasmussen Andmentioning
confidence: 99%